A Rose By Any Other Name Might Be More Noticed: Attracting Journalists’ Attention in the Digital Age - Terence L. Day (Journal of Applied Communications, 2003)
An article in the Sept.12, 2002, issue of Media Insider reported PR Newswire’s media relations team visits hundreds of newsrooms each month where it has observed many different schemes for managing information. The author suggested peppering news releases with variations of keywords news releases or archived information on Web sites. This paper reports an informal testing of search engines and words that might commonly appear in news releases and other documents written by land-grant university communicators. Searches for 54 words or phrases [Table 1] on Web sites maintained by two popular newspapers, two land-grant universities, and the U.S. Department of Agriculture corroborated the Media Insider author’s assertion that expanding use of keywords will increase prospects of being found by journalists who use search engines. Further, the study indicated that nomenclatures popular with educators may reduce prospects for media exposure.